Μελέτη της επίδρασης του υποστρώματος στα δομικά χαρακτηριστικά λεπτών υμενίων κολλαγόνου με χρήση Μικροσκοπίας Ατομικής Δύναμης - Κοντός, Λεωνίδας (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ηλεκτρολόγων Μηχανικών και Μηχανικών Υπολογιστών. Τομέας Ηλεκτρομαγνητικών Εφαρμογών Ηλεκτροοπτικής και Ηλεκτρονικών Υλικών. Εργαστήριο Βιοϊατρικής Οπτικής και Εφαρμοσμένης Βιοφυσικής, 2014)
Collagen, as the most abundant protein in the human body (25% -35%) and basic building block of tissues with the high biological significance, such as tendons and skin, is a key research study with its use in biomedical applications. In the current study, imaging of collagen was attempted in two separate substrates, mica because of the possibility to easily create almost atomic flat surface (perfect basal cleavage), and polystyrene spheres, because of the possibility of forming hexagonal arrays, allowing the collagen to acquire a specific structure and direction, which is very important for nanotechnology applications. For this reason, an atomic force microscope (AFM) was used for imaging of the experiments with the collagen and substrates, thanks to its capability of measuring in nanometer scale. The AFM with the two imaging modes contact and non-contact (by topography and phase, known as tapping) gave different results for the two methods, with the tapping method demonstrated (at least for the experimental data) more effective imaging of collagen and substrates.